Analyzing the Effects of TikTok on Youth Psychological Well-Being: A Systematic Literature Review [Analisis Kesan Aplikasi TikTok Terhadap Kesejahteraan Psikologi Belia: Sorotan Literatur Bersistematik] - Mazura @ Mastura binti Muhammad (Tanjung Malim, 2024)
Analyzing the Effects of TikTok on Youth Psychological Well-Being: A Systematic Literature Review [Analisis Kesan Aplikasi TikTok Terhadap Kesejahteraan Psikologi Belia: Sorotan Literatur Bersistematik] by Mazura @ Mastura binti Muhammad